2014
DOI: 10.1007/s12105-014-0558-0
|View full text |Cite
|
Sign up to set email alerts
|

Adamantinoma-Like Ewing Sarcoma Mimicking Basal Cell Adenocarcinoma of the Parotid Gland: A Case Report and Review of the Literature

Abstract: Adamantinoma-like Ewing sarcoma (AES) is a rare variant of the Ewing family of tumors that resembles classic adamantinoma of bone. AES shows epithelial differentiation and a more complex immunohistochemical expression profile with keratin and basal marker immunoreactivity and can resemble a variety of carcinomas. We report an unusual case of an AES of the parotid gland that mimicked a basal cell adenocarcinoma. Like basal cell adenocarcinoma, this AES showed a nested basaloid proliferation with peripheral pali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 28 publications
(25 reference statements)
0
39
0
Order By: Relevance
“…Recent studies have demonstrated rare examples exhibiting prominent squamous epithelial differentiation, for which the designation of “adamantinoma-like” EFT or EFT with complex epithelial differentiation has been proposed. (10, 1318) The degree to which these tumors truly resemble adamantinomas is certainly debatable, but this terminology is historical: the term adamantinoma-like EFT was used since the first few reported cases with this phenotype occurred in the long tubular bones, including tibia and simulated the diagnosis of extragnatic adamantinoma. (10, 13, 14) Only recently similar cases were documented in the head and neck.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have demonstrated rare examples exhibiting prominent squamous epithelial differentiation, for which the designation of “adamantinoma-like” EFT or EFT with complex epithelial differentiation has been proposed. (10, 1318) The degree to which these tumors truly resemble adamantinomas is certainly debatable, but this terminology is historical: the term adamantinoma-like EFT was used since the first few reported cases with this phenotype occurred in the long tubular bones, including tibia and simulated the diagnosis of extragnatic adamantinoma. (10, 13, 14) Only recently similar cases were documented in the head and neck.…”
Section: Discussionmentioning
confidence: 99%
“…(22) The remaining six cases were diagnosed prospectively in the authors’ respective consultation practices (JAB, RSS, and CRA). One of these cases (case 4) was previously published as a case report,(18) and another case (case 3) was included as part of a series of soft tissue myoepithelial carcinomas due to its EWSR1 gene rearrangement. (23, 24) Each case was examined by routine light microscopy, immunohistochemistry, and fluorescence in situ hybridization (FISH).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Diagnostic pitfalls stem from the epithelial features identified in these tumors, such as squamoid pearls, intra-epithelial growth, as well as immunoreactivity for epithelial markers. As carcinomas typically outnumber round cell sarcomas in the H&N, the more common entities that adamantinoma-like ES were confused with were: basaloid squamous cell carcinoma, basal cell adenocarcinoma [25], and sinonasal undifferentiated/poorly differentiated carcinoma [19]. The young age at diagnosis and the diffuse/ strong membranous pattern of CD99 reactivity are important clues for a diagnosis of adamantinoma-like ES, which should trigger additional molecular testing.…”
Section: Discussionmentioning
confidence: 99%